2013
DOI: 10.1371/journal.pone.0054057
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Variations Induced by Wheat-Rye 2R and 5R Monosomic Addition Lines

Abstract: BackgroundMonosomic alien addition lines (MAALs) can easily induce structural variation of chromosomes and have been used in crop breeding; however, it is unclear whether MAALs will induce drastic genetic and epigenetic alterations.Methodology/Principal FindingsIn the present study, wheat-rye 2R and 5R MAALs together with their selfed progeny and parental common wheat were investigated through amplified fragment length polymorphism (AFLP) and methylation-sensitive amplification polymorphism (MSAP) analyses. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…In fact, since Barbara McClintock's intuition that "species crosses are another potent source of genome modification that could yield TE activation" [72], a large body of evidence has demonstrated that the merging of parental species in hybrids and allopolyploids can lead to a "genomic shock", which triggers the dysregulation of normal cell functions and various forms of pertubations, almost invariably resulting in activation of previously silent transposable elements (TEs) [73][74][75]. Besides that in complete interspecific hybrids, epigenetic changes, particularly the alteration of DNA methylation patterns, have been observed in introgression lines of rice [76,77] and wheat [78,79] involving even sub-chromosomal amounts of alien chromatin. In some such contexts, sequences that were corresponding to TEs were shown to be the main target of altered DNA methylation [79].…”
Section: Recmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, since Barbara McClintock's intuition that "species crosses are another potent source of genome modification that could yield TE activation" [72], a large body of evidence has demonstrated that the merging of parental species in hybrids and allopolyploids can lead to a "genomic shock", which triggers the dysregulation of normal cell functions and various forms of pertubations, almost invariably resulting in activation of previously silent transposable elements (TEs) [73][74][75]. Besides that in complete interspecific hybrids, epigenetic changes, particularly the alteration of DNA methylation patterns, have been observed in introgression lines of rice [76,77] and wheat [78,79] involving even sub-chromosomal amounts of alien chromatin. In some such contexts, sequences that were corresponding to TEs were shown to be the main target of altered DNA methylation [79].…”
Section: Recmentioning
confidence: 99%
“…Besides that in complete interspecific hybrids, epigenetic changes, particularly the alteration of DNA methylation patterns, have been observed in introgression lines of rice [76,77] and wheat [78,79] involving even sub-chromosomal amounts of alien chromatin. In some such contexts, sequences that were corresponding to TEs were shown to be the main target of altered DNA methylation [79].…”
Section: Recmentioning
confidence: 99%
“…Another study investigated the genetic stability of wheat-rye ("Chinese Spring" x "Imperial") disomic addition lines, by using the Feulgen method and fluorescent in situ hybridization (Szakács and Molnár-Láng, 2010). Subsequent research on wheat-rye 2R and 5R indicated that wheat-rye monosomic addition lines could induce different and drastic genetic/epigenetic variations, and these variations might not be caused by introgression of rye chromatins into wheat (Fu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome instability and genome rearrangements in wheat-rye addition lines have also been observed (Bento et al, 2010;Szakács and Molnár-Láng, 2010). Drastic genetic and epigenetic variations were induced by wheat-rye 2R and 5R monosomic addition lines (Fu et al, 2013).…”
Section: Introductionmentioning
confidence: 92%
“…In recent years, modern cultivation systems have given rise to the sharp loses of wheat genetic diversity. Genetic erosion makes wheat increasingly vulnerable to biotic and abiotic stresses [25]. On the other hand, the increase of world population and the decrease in acreage of farmland require a much higher wheat yield to meet the need of humankind.…”
Section: Introductionmentioning
confidence: 99%